Cambrian marine radial cerebroid ooids: Participatory products of microbial processes. (22nd June 2021) - Xiao, Enzhao; Riaz, Muhammad; Zafar, Tehseen; Latif, Khalid
Abstract : The Cambrian Miaolingian Series strata at the Kouquan section, North China, are primarily divided into the Xuzhuang, Zhangxia, and Gushan formations. This particular series comprises oolitic limestone in the middle to upper intervals. Thin section observations of carbonate rock samples from the Zhangxia Formation show that the well‐preserved and most remarkable grains among them are cerebroid ooids. Although these ooids have characteristic serrated margins, they are distinct from ooids reported in previous publications due to inconspicuous concentric laminae and radial structures composed of micrite and microspar. To understand the origin of these ooids, we employed petrographic examination, X‐ray diffraction (XRD), scanning electron microscopy (SEM), electron probe microanalysis (EPMA), and isotope analyses to explore their compositions and conditions of development. In addition, the occurrence of these cerebroid ooids is closely related to that of dark‐coloured micrite: most cerebroid ooids and quasi‐cerebroid ooids float inside dark micrite; dark micrite appears in the interior of cerebroid ooids as a radial micrite structure. EPMA and energy‐dispersive X‐ray (EDX) spectroscopy analyses of micrite reveal that the dark micrite consists of lithomicrobial mats. Fine‐scale characterization of the dark micrite inside these cerebroid ooids shows the presence of filamentous and bowl‐shaped calcified microbial fossils and extracellular polymeric substance (EPS) calcified remnants. Isotopic data indicate a variation of δ 13 C isotopic values between −4.92‰ and −0.11‰ (VPDB) and −9.89‰ and −4.93‰ for δ 18 O values (VPDB). The negative values of δ 13 C in the studied ooid suggest the genesis of carbon from the high organic‐rich zone such as the microbial zone. Also, the 13 C‐depleted carbon values in the ooids advocate that the carbon is mainly derived from organic sources associated with the sulphate reduction bacterial activity. Thus, isotopic data of this study also provide consistent clues in favour of microbial participation during the genesis of cerebroid ooids. In conclusion, our new findings strongly confirm that the cerebroid ooids of the North China Platform are genetically related to microbial processes. Abstract : Geochemical attributes of the Cambrian radial cerebroid ooids of the North China Platform: (a) represents the remnants of organic matter inside the dark micrite; (b) filamentous microbial fossils (fm) and bowl‐shaped microbial fossil community (bm) along with the extracellular polymeric substance (EPS); (c) calcified microbial mat remnants; and (d) carbon and oxygen isotopic variations.